Optical sensors for power transformer monitoring: A review. Issue 3 (27th October 2020) - Ma, Guoming; Wang, Yuan; Qin, Weiqi; Zhou, Hongyang; Yan, Chao; Jiang, Jun; Ju, Yiguang
Abstract: Power transformers play a vital role in power transmission systems from the energy source to the consumption center. In situ diagnostics of the performance of power transformers provides a variety of benefits to ensure reliable electricity transmission. Immunity to electromagnetic interference, high sensitivity, high insulation as well as small dimensions of optical sensing make it very attractive for applications in power transformer monitoring. This paper presents a critical review of various diagnostic methods for power transformers such as partial discharge, dissolved gases, temperature and other important sensing, and optical detection. The advantages and disadvantages of different monitoring methods are carefully discussed and assessed. Finally, the existing technical barriers and future prospects of optical monitoring methods for power transformers are presented.